Pengemabngan LKPD Berbasis Potensi Lokal Terintegrasi Keterampilan Abad 21 Pada Materi Ekosistem Kelas X SMA Negeri 2 Halmahera Barat - Asri Fara; Ade Haerullah; Abdu Masud (Peneliti.net, 2023)
Biology learning in the 2013 curriculum provides opportunities for teachers to be able to take advantage of the local potential that exists around the school to be used as teaching materials. Regarding this, only educators or teachers can understand and know the environmental conditions and character of students, so teachers play an important role in innovating learning so that learning objectives are achieved. The purpose of this study is to find out the feasibility of integrated local potential-based LKPD in the 21st century on class X ecosystem material at SMAN 2 West Halmahera. This type of research is research and development (R&D) with the ADDIE development model. ADDIE stands for Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used in this study were interviews, questionnaires, documentation and instruments. The results showed that the development of LKPD based on local potential integrated 21st century skills in the class X ecosystem material at SMAN 2 West Halmahera with very suitable criteria for use based on the average results on aspects of biological material of 87.98, 21st century learning aspects of 88.08, the integrated learning aspect of local potential is 88.78 and the language aspect is 86.75.